2021
DOI: 10.1101/2021.01.05.425449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel skeletal-specific adipogenesis pathway defines key origins and adaptations of bone marrow adipocytes with age and disease

Abstract: SUMMARYBone marrow adipocytes (BMAs) accumulate with age and in diverse disease states. However, their age- and disease-specific origins and adaptations remain unclear, impairing our understanding of their context-specific endocrine functions and relationship with surrounding tissues. In this study, we identified a novel, bone marrow-specific adipogenesis pathway using the AdipoqCre+/DTA+ ‘fat free’ mouse (FF), a model in which Adipoq-Cre drives diphtheria toxin-induced cell death in all adiponectin-expressing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Of note, cBMAT starts to appear during embryogenesis and/or in early childhood whereas the development of rBMAT is thought to occur later in life and during aging in particular (Li et al, 2018;Suchacki et al, 2020;Robles et al, 2021). The transplantation of red bone marrow to ectopic sites results in the formation of a hematopoietic bone marrow nodule at the site of transplantation.…”
Section: Unique Characteristics Of Bone Marrow Adipocytesmentioning
confidence: 99%
“…Of note, cBMAT starts to appear during embryogenesis and/or in early childhood whereas the development of rBMAT is thought to occur later in life and during aging in particular (Li et al, 2018;Suchacki et al, 2020;Robles et al, 2021). The transplantation of red bone marrow to ectopic sites results in the formation of a hematopoietic bone marrow nodule at the site of transplantation.…”
Section: Unique Characteristics Of Bone Marrow Adipocytesmentioning
confidence: 99%
“…After this, Leilei Zhong presented new data that defines a stromal/ perivascular, adiponectin-expressing bone marrow adipocyte progenitor, termed the marrow adipogenic lineage precursor (MALP) and its role in the maintenance of the bone marrow vasculature (34,35). Last, Xiao Zhang showed that a unique population of maladapted bone marrow adipocytes was retained in an otherwise 'fat free' lipodystrophic mouse, revealing the existence of a bone-specific, compensatory adipogenesis pathway that is activated in states of metabolic stress (36). Overall, this session contributed to our understanding of the unique cellular origins of bone marrow adipocytes during development and metabolic disease, in addition to providing new information about the molecular signals regulating the maturation of committed pre-adipocytes within the bone marrow.…”
Section: Session Vi: Bone Marrow Adipose Tissue Origins and Maturationmentioning
confidence: 99%